Individuals Family History Positive for Alcoholism Show Functional Magnetic Resonance Imaging Differences in Reward Sensitivity That Are Related to Impulsivity Factors - Andrews, Melissa M.; Meda, Shashwath A.; Thomas, Andre D.; Potenza, Marc N.; Krystal, John H.; Worhunsky, Patrick; Stevens, Michael C.; O'Malley, Stephanie; Book, Gregory A.; Reynolds, Brady; Pearlson, Godfrey D. (Biological psychiatry (1969), 2011)
Substance-abusing individuals tend to display abnormal reward processing and a vulnerability to being impulsive. Detoxified alcoholics show differences in regional brain activation during a monetary incentive delay task. However, there is limited information on whether this uncharacteristic behavior represents a biological predisposition toward alcohol abuse, a consequence of chronic alcohol use, or both. We investigated proposed neural correlates of substance disorder risk by examining reward system activity during a monetary incentive delay task with separate reward prospect, reward anticipation, and reward outcome phases in 30 individuals with and 19 without family histories of alcoholism. All subjects were healthy, lacked DSM-IV past or current alcohol or substance abuse histories, and were free of illegal substances as verified by a urine toxicology screening at the time of scanning. Additionally, we explored specific correlations between task-related nucleus accumbens (NAcc) activation and distinct factor analysis-derived domains of behavioral impulsivity. During reward anticipation, functional magnetic resonance imaging data confirmed blunted NAcc activation in family history positive subjects. In addition, we found atypical activation in additional reward-associated brain regions during additional task phases. We further found a significant negative correlation between NAcc activation during reward anticipation and an impulsivity construct. Overall, results demonstrate that sensitivity of the reward circuit, including NAcc, is functionally different in alcoholism family history positive individuals in multiple regards.